Leveraging on Agricultural Entomology in Precision Farming for Sustainable Agriculture and Food Security - Zakka, Usman; Lawal, Olanrewaju; Nwosu, Luke Chinaru (Canadian Journal of Agriculture and Crops, 2019)
Leveraging on agricultural entomology in precision farming for sustainable agriculture, food security and other environmental benefits was reviewed. Precision farming (PF) is a new approach to farm management, a strategy in which detailed and location-specific information is employed to precisely manage farm production inputs. The strategy ensures that farm production inputs such as pesticides, herbicides, seed, fertilizer and water are best utilized to achieve sustainability when applied where necessary and as required. PF leads to cost reduction, efficient use of production inputs, increasing size and scope of farming operations without additional labour cost, improvement in site selection and improvement in production process control, improvement in record keeping and product tracking and reduction of potential pollution. The suggested technologies in precision farming include global positioning system, equipment guidance system, mapping software, precision crop input application technologies and yield monitoring systems. These components should be organized into essential building blocks in order to create a functional system. The roles of agricultural entomology in precision farming for sustainable agriculture and food security were discussed. Precision farming, a veritable tool to fight against insect pest, the new frontiers in insect pest management and the application of precision farming in integrated pest management were also discussed. The utilization of low cost technologies for precision farming was advised- to improve effectiveness of farming operations, thereby boosting agricultural production to enhance sustainability and ensure food security.